The Impact of Unemployment, Inflation, and Participation Rate of Women in Labor Market on Divorce Process in Iran - Hasan Aama Bandeh Gharaei; Seyed Mohammad Seyedi; Hamed mokhtaritorshizi; Narges Salehnia (فصلنامه رفاه اجتماعی, 2023)
Introduction: The decrease in the marriage rate and the increase in the divorce rate in the last few decades are among the changes in the family institution. The growth of the divorce rate is considered as one of the severe harms of the change in the family institution, which brings with it the expansion of numerous social problems. The status of the economic factor is an influencing factor in divorce because economic disturbances cause quarrels and conflicts between the spouses, other effective factors are social and culture status, etc. There is a parallel relationship between the trends of macroeconomic developments in Iran and the trend of divorce. On the one hand, the unfavorable situation of Iran's macroeconomic variables and on the other hand, the significant increase in the number of divorces in Iran for the past few decades, make it important and necessary to examine the impact of macroeconomic indicators on divorce. Method: The two-stage least squares method has been used to investigate the effect of economic variables on the divorce process in Iran (1370-1400; 1991-2021). The estimation of the equations has been done in a systematic way. This issue has been analyzed with the help of simultaneity bias and diagonality test. From identification problem over specified equations are confirmed. Findings: The results show that the effect of unemployment and inflation on divorce is likely to be significant, their coefficients are equal to 0.70 and 0.14. There is a direct relationship between women's participation in the market and the divorce rate; its coefficient is 0.74. Also, there is a simultaneous relationship between the average age of women at first marriage, this variable, and the divorce rate. Discussion: The economy is an influential factor in couples' decision to get divorced. Therefore, to reduce its rate, the unfavorable situation of economic variables should be improved. The role of women's participation rate in the labor market is significant, but it should be noted that part of it can be due to the previous context. That is, couples have decided to divorce, due to bad economic conditions, social disturbances, personal factors, etc., but women's lack of independence has been an obstacle to divorce, with the woman's employment, ultimately, divorce takes place.